Lessons and Policy Implications from the Global Financial Crisis - Claessens, Stijn; Dell'Ariccia, Giovanni; Igan, Deniz; Laeven, Luc. (Washington, D.C. : International Monetary Fund, 2010)
The ongoing global financial crisis is rooted in a combination of factors common to previous financial crises and some new factors. The crisis has brought to light a number of deficiencies in financial regulation and architecture, particularly in the treatment of systemically important financial institutions, the assessments of systemic risks and vulnerabilities, and the resolution of financial institutions. The global nature of the financial crisis has made clear that financially integrated markets, while offering many benefits, can also pose significant risks, with large real economic consequences. Deep reforms are therefore needed to the international financial architecture to safeguard the stability of an increasingly financially integrated world.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet